2007
DOI: 10.1177/1098611106287776
|View full text |Cite
|
Sign up to set email alerts
|

Drug Law Enforcement

Abstract: This article describes the results of a systematic review of drug law enforcement evaluations. The authors describe the search procedures and document the results in five main categories: international/national interventions (e.g., interdiction and drug seizure), reactive/ directed interventions (e.g., crackdowns, raids, buy-busts, saturation patrol, etc.), proactive/ partnership interventions (e.g., third-party policing, problem-oriented policing, community policing, drug nuisance abatement, etc.), individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The “war on drugs” affected law enforcement agencies as they implemented policies that mirrored a war mentality (Bobo & Thompson, 2006; Mazerolle, Soole, & Rombouts, 2007; Parsons, 2017) including (a) creation of drug courier profiles (characteristics of individuals who might be transporting drugs), (b) implementation of Stop and Frisk (warrantless searches on suspicious individuals who might be carrying drugs or be dangerous), (c) conducting investigatory traffic stops (stop for minor traffic violations to question people who might be involved in drug activity), and/or (d) training canine units to detect illegal drugs. This new enforcement-oriented policing was perceived as an effective and successful approach to secure the safety of the community from illegal substances (Bobo & Thompson, 2006; Mazerolle et al, 2007; Zimmer, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The “war on drugs” affected law enforcement agencies as they implemented policies that mirrored a war mentality (Bobo & Thompson, 2006; Mazerolle, Soole, & Rombouts, 2007; Parsons, 2017) including (a) creation of drug courier profiles (characteristics of individuals who might be transporting drugs), (b) implementation of Stop and Frisk (warrantless searches on suspicious individuals who might be carrying drugs or be dangerous), (c) conducting investigatory traffic stops (stop for minor traffic violations to question people who might be involved in drug activity), and/or (d) training canine units to detect illegal drugs. This new enforcement-oriented policing was perceived as an effective and successful approach to secure the safety of the community from illegal substances (Bobo & Thompson, 2006; Mazerolle et al, 2007; Zimmer, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Coordinated interventions have the potential to disrupt the harm caused by gang members through large-scale drug distribution and gun violence, while attempting to reverse some of the physical and social incivilities brought on certain neighborhood corners that affect residents' quality of life. Indeed, in their systematic review of drug law enforcement, (Mazerolle et al 2007) found that proactive strategies involving partnerships between law enforcement and third parties or community agencies were the most effective at reducing drug and other crime, as well as increasing community residents' reported quality of life (Mazerolle et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…First, we strongly recommend that future research rigorously examines the impact of drug supplier arrest and seizures, with a particular focus on collecting high-quality longitudinal data to permit sophisticated analysis that can answer nuanced questions with implications for policing practice (see eg Singleton et al 2018); for example, the seizure and arrest thresholds that are required to disrupt drug markets and sustain those disruptions. Second, we recommend that policymakers, funding bodies and practitioners consider the use of proactive law enforcement initiatives that are place-focused and problem-focused, which have a stronger evidence base (eg see Mazerolle, Soule & Rombouts 2007;Mazerolle, Eggins & Higginson 2020).…”
Section: Discussionmentioning
confidence: 99%